Практическая реализация и исследование релейно-робастных алгоритмов управления синхронными электродвигателями - Полилов, Егор Владимирович; Батрак, Андрей Михайлович; Мотченко, Александр Иванович; Руднев, Евгений Сергеевич (НТУ "ХПИ", 2010)
The possibility of creating a universal stand for the practical implementation and research new Closed-relay-robust control algorithms for functional and parametric uncertain electromechanical systems based on AC Motors is shown. At the program level implemented discontinuous control algorithms for a synchronous machine with excitation from permanent magnets when powered from the frequency converter Sinamics S120.
Practical implementation and research of the relay type and robust control algorithms of synchronous motors
Keywords: система электромеханическая; процесс технологический; стенд экспериментальный; магнит постоянный; преобразователь частоты; модель математическая